-20z+3=-19z+18

Simple and best practice solution for -20z+3=-19z+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20z+3=-19z+18 equation:


Simplifying
-20z + 3 = -19z + 18

Reorder the terms:
3 + -20z = -19z + 18

Reorder the terms:
3 + -20z = 18 + -19z

Solving
3 + -20z = 18 + -19z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '19z' to each side of the equation.
3 + -20z + 19z = 18 + -19z + 19z

Combine like terms: -20z + 19z = -1z
3 + -1z = 18 + -19z + 19z

Combine like terms: -19z + 19z = 0
3 + -1z = 18 + 0
3 + -1z = 18

Add '-3' to each side of the equation.
3 + -3 + -1z = 18 + -3

Combine like terms: 3 + -3 = 0
0 + -1z = 18 + -3
-1z = 18 + -3

Combine like terms: 18 + -3 = 15
-1z = 15

Divide each side by '-1'.
z = -15

Simplifying
z = -15

See similar equations:

| 8*20= | | -7x+25+2x=10 | | 56b-7=7+56b | | X^2+(-6x)=-9 | | 3y-1y+2y-5=7-2y+5 | | r/6=-2 | | sin50=x/21 | | 3(16x-24)+2= | | -13r+8r=10 | | 2(m+4)=8+2m | | 5x+8=98 | | 24+3x-6=9 | | .5b+7=22 | | -3x+5x-7=2(x-2)-5 | | -k-3=4-2k | | 5x+3=-x-27 | | 2+3r-4r=2 | | 10c-8/3-4c=6c | | e^0=x | | -13r-8r=10 | | 6h+8=5h | | (11x+4)=180 | | x^2-6x+y^2-4y-13=0 | | 6m(m+16)(m-13)=0 | | .25(8x+28)-19=-.40(30x-45) | | 10-7s=-3s-2s-10 | | 42=2x+6 | | 13x-(9+2(x+4))= | | -69-5x=3x+27 | | 1/1.75-2 | | -2-3y+2y=-13 | | 23-2c=14 |

Equations solver categories